P5_3 Probability of Meeting a Doppelgänger - Singh, Jagraj; Agrawal, Rusi; Ruprai, Amrik; Shaikh, Hasan (Physics Special Topics, 2021)
This paper investigates the idea of doppelg¨angers and the probability of meeting an unrelated but biologically identical person in an average lifetime. The probability is calculated to be 1.5×10−17 , showing that the probability of meeting a doppelg¨anger is highly unlikely yet theoretically possible.